STRATEGI CUSTOMER SERVICE BANK SYARIAH INDONESIA KCP GUNUNG KIDUL WONOSARI DALAM MENINGKATKAN PELAYANAN PRIMA TERHADAP PRINSIP SYARIAH - Vivi Lutfiatin Atin; Luthfi Hadi Aminuddin (Institut Agama Islam Muhammadiyah Sinjai, 2022)
Bank Syariah Indonesia is a financial institution that is engaged in services based on sharia principles. Where the bank must prepare qualified, trustworthy, obedient to bank operations and have a good service strategy so that the bank is able to provide services and handle various customer complaints. In this case, customer service is the key to success in banking activities. This study aims to: (1) find out customer service in improving excellent service to sharia principles, (2) find out customer service strategies in improving excellent service to sharia principles, (3) find out the impact of service in improving excellent service to sharia principles. In this study, the author uses a qualitative approach and the type of research (field research), data collection techniques by means of interviews and documentation. Furthermore, data analysis using the description method. The data source is Bank Syariah Indonesia KCP Gunung Kidul Wonosari. Based on the results of the study, it can be concluded that the strategy used by customer service at Bank Syariah Indonesia KCP Gunung Kidul Wonosari to improve excellent service to sharia principles is customer service in providing services to its customers, namely using the basic strategy of being friendly, responsive, and good name tags. always considered, while the main strategies are Responsiveness (Quick Respond), Competence (competence), Credibility (trustworthy), Contribution (contribution), Honesty (honesty), Service Excellent (excellent service), Innovation (change). Strategi customer service bank syariah Indonesia Kcp gunung Kidul Wonosari dalam meningkatkan pelayanan prima terhadap prinsip syariah. Penelitian ini bertujuan untuk: mengetahui pelayanan, Strategi dan dampak pelayanan dalam meningkatkan pelayanan prima terhadap prinsip syariah. Dalam penelitian ini penulis menggunakan pendekatan kualitatif dan jenis penelitian (field research), teknik pengumpulan data dengan cara wawancara dan dokumentasi dengan memakai analisis data menggunakan metode deskripsi. Data yang menjadi sumber adalah Bank Syariah Indonesia KCP Gunung Kidul Wonosari. Berdasarkan hasil penelitian, dapat disimpulkan bahwa strategi yang digunakan customer service Bank Syariah Indonesia KCP Gunung Kidul Wonosari untuk meningkatkan pelayanan prima terhadap prinsip syariah adalah pelayanan customer service dalam memberikan pelayanan kepada nasabahnya yaitu menggunakan strategi dasar yaitu bersikap ramah, cepat tanggap, dan name tag yang selalu diperhatikan, sementara strategi utamanya adalah Responiveness (Cepat Tanggap), Competence (kompetensi), Credibility (dapat dipercaya), Contribution (kontribusi), Honesty (kejujuran), Service Excellent (pelayanan prima), Innovation (perubahan).